Processes of Communication Family Divorced in Decision-Making The boy to Build Independence - Ansa Ferani; Dr. Dra. Sri Budi Lestari, SU (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2016)
Families have many of the functions, one of them is The Child Socialization Role which teaches children to be sociable and adapt to its environment. The achievement of independence to someone especially boys is one of the success indicators of parents who run the family functions as The Child Socialization Role. But this process will experience the difference when the family through divorce. Parental divorce giving effect directly to children through numbers, the phenomenon, and stereotype in the community This research aims to knowing the process of the establishment of independence in decision-making of boy in divorced families. Chosen boys in this research is driven by a phenomenon in the community who hinted that a boy who came from families divorced having bad behavior, not thought long and not skilled in making a decision as one indicator of self-reliance. This research will be examined by using qualitative methods and phenomenology analysis. Theory as well as the concept that used on this research are, The Roles Theory, Relational Dialectics Theory, Nurturing and Control Theory, Verbal Communication and Nonverbal Communication Theory, as well as the concept of Communication Familiar Intercourse (Family Communication). To research is found that relationship created between the parent who lived together own partnership in the relation of a son and parents.When their relationship stay go well after the divorce, there are the process of adapting not return and can encourage them contribute in form a connection with a positive image of which will affect children setting the future. The cycle of development relations contributed on a communication a family of informants after the divorce, this is shown via relationship several informants that flourish with the openness and informants other that does not develop after the divorce. This research is also found that the role of extended family like a grandfather, uncle, and bude is very influence, it stimulate them to make a good relations between the boy and his parents. Good communication between the parents who lived together and the boy will form trust that can make a boy can take his decision by himself as one of independence indicator. Independence that created in someone can be realized through decision-making. Not only communication that can make this success but also the role and the nurturing patterns of parents who used. This research also expresses that family members can have more than one roles after divorce, it is happens not only in parents roles but also the boys. The double role can support the sense of responsibility and maturity of boys, both in the emotion, behavior and thought. The difference of nurturing pattern can be happened because of the situation, it will driving maturity and independence through decision-making in themself who came from divorced families.